Is Polymerase Chain Reaction Positivity More Common in Patients with COVID-19 Pneumonia with Fever? - Emel Cireli; Aydan Mertoğlu; Günseli Balcı; Aylin Bayram; Nil Kuranoğlu; Ali Kadri Çırak (Dubai Medical Journal, 2022)
Introduction: There is conflicting data about the rate of fever at admission and during hospitalization in COVID-19 pneumonia. We analyzed the rate of fever in our patients to find the diagnostic value of fever and to predict PCR status in COVID-19. Methods: It was a retrospective cross-sectional study conducted in the Health Sciences University Dr. Suat Seren Chest Diseases and Chest Surgery Training and Research Hospital, which was a tertiary chest diseases pandemic hospital in İzmir. We included 389 patients hospitalized for COVID-19 and analyzed them according to PCR status and presence of fever. Fever was defined as temperature over 38°C. Results: Thirty-eight percentage of our patients complained of fever before admission. However, when they were admitted, only 13.6% of them had objective high fever. 26.5% had high fever during hospital stay. PCR-positive patients had less comorbidity. More of PCR-positive patients had fever in the course of hospitalization and their length of hospital stay was longer and mortality was higher. Although we expected to find a high sensitivity, the sensitivity of high fever in our settings was low. Sensitivity, specificity, positive, and negative predictive values of high fever at admission in predicting the positivity of the PCR test were 16.9%, 90.6%, 69.8%, and 45.8%, respectively. Sensitivity, specificity, positive, and negative predictive values of high fever during hospitalization to predict the positivity of PCR test were 36.1%, 85.9%, 76.7%, and 51.0%, respectively. Conclusion: 13.6% of our COVID-19 patients had objective high fever at admission. 26.5% had high fever during hospital stay. PCR-positive patients had less comorbidity. More PCR-positive patients had fever in the course of hospitalization and their length of hospital stay was longer and mortality was higher. Although we expected to find a high sensitivity, the sensitivity of high fever in our settings was lower than expected. Temperatures <38°C at admission and during hospitalization determine 90.6% and 85.9% of the PCR-negative patients, respectively. These high specificity values imply that if the PCR test is negative, the patient’s temperature is more likely to be lower than 38°C.